Ethnobotanical Study of Medicinal Plants Used To Treat Human Diseases In The Urban Forest Area Of Sangga Buana Cilandak Jakarta Selatan - Nadya Siahaan; Dinda Triskaprilia; Muhamad Angga; Adelia Trisna; Dyah Larasati; Sri Endarti Rahayu; Julianti Siburian (Journal of Tropical Biodiversity, 2022)
Indonesia has abundant natural resources. Natural resources can be used as medicinal herbs. The use of natural resources using medicinal plants (medicinal herbs) has existed for a long time. Medicinal plants are spread all over Indonesia. The urban forest of Sanga Buana Cilandak in South Jakarta is widely used as a place for conservation, education and nature-based tourism, and is selected as a research site because it is used by local people for food and medicine. The purpose of this study was to identify which plants were used as medicines by people in the Sangabuana area. Survey data collection is based on the results of surveys obtained through direct interviews with the community at the destination. Interviews were conducted using a purposive sampling method. Purposive sampling is sampling that is limited to a specific target group. We interviewed seven respondents working in the urban forests of Sangabuana. Our research has revealed 56 species of medicinal plants belonging to 30 families. The most commonly used part of the plant as a medicine is the leaves, and the most common processing method is boiled. Based on utility value (UV) and fidelity level (FL) calculations, red ginger (Alpinia purpurata) UV is shown to have 1.43 and FL to be 100%.